The Middle Class Consensus and Economic Development - Easterly, William (World Bank, Washington, DC, 2014)
Modern political economy stresses "society's polarization" as a determinant of development outcomes. Among the most common dorms of social conflict are class polarization, and ethnic polarization. A middle class consensus is defined as a high share of income for the middle class and a low degree of ethnic polarization. A middle class consensus distinguishes development successes from failures. A theoretical model shows how groups - distinguished by class or ethnicity - will under-invest in human capital and infrastructure when there is "leakage" to another group. The author links the existence of a middle class consensus to exogenous country characteristics, such as resource endowments, along the lines of the provocative thesis of Engerman and Sokoloff (1997), that tropical commodity exporters are more unequal than other societies. The author confirms this hypothesis with cross-country data. This makes it possible to use resource endowments as instruments for inequality. A higher share of income for the middle class and lower ethnic polarization, are empirically associated with higher income, higher growth, more education, better health, better infrastructure, better economic policies, less political instability, less civil war (putting ethnic minorities at risk), more social "modernization," and more democracy.